Role Balance and Work-Life Stress Among Balinese Hindu Women Auditors - Adnyani, Ida Ayu Ary Putri; Rasmini, Ni Ketut; Suaryana, I Gusti Ngurah Agung; Wirajaya, I Gde Ary (Jurnal Ilmiah Akuntansi dan Bisnis, 2025)
This study explores the role balance of Balinese Hindu women auditors and its impact on work-life stress, focusing on an informant who has successfully balanced her role as a single parent and a senior auditor at the Bali Provincial Development and Finance Supervisory Agency. Using a phenomenological approach with an interpretive qualitative design, this study aims to understand how the informant successfully manages her dual roles within Bali's solid cultural context. The research findings reveal that the informant can balance her dual roles dynamically and holistically. She prioritizes her family as the primary focus while still dedicating herself to her professional duties. The work-life stress management strategies employed by the informant involve flexibility, adaptability, and high commitment to both of her roles. The results of this study provide in-depth insights into how Balinese Hindu women can successfully balance their dual roles as Balinese Hindu women working as auditors. The implications of this study include a better understanding of the challenges and strategies needed to achieve work-life balance, especially within a culturally rich context such as Bali. This study contributes theoretically to the literature on role balance and work-life stress. It provides practical insights for individuals and organizations in supporting the well-being and productivity of Balinese Hindu women with dual roles.